Engineering Tunable Ratiometric Dual Emission in Single Emitter‐based Amorphous Systems - Sun, Hao; He, Menglu; Baryshnikov, Glib V.; Wu, Bin; Valiev, Rashid R.; Shen, Shen; Zhang, Man; Xu, Xiaoyan; Li, Zhongyu; Liu, Guofeng; Ågren, Hans; Zhu, Liangliang (Angewandte Chemie, 2024)
Molecular emitters with multi‐emissive properties are in high demand in numerous fields, while these properties basically depend on specific molecular conformation and packing. For amorphous systems, special molecular arrangement is unnecessary, but it remains challenging to achieve such luminescent behaviors. Herein, we present a general strategy that takes advantage of molecular rigidity and S1‐T1 energy gap balance for emitter design, which enables fluorescence–phosphorescence dual‐emission properties in various solid forms, whether crystalline or amorphous. Subsequently, the amorphism of the emitters based polymethyl methacrylate films endowed an in situ regulation of the dual‐emissive characteristics. With the ratiometric regulation of phosphorescence by external stimuli and stable fluorescence as internal reference, highly controllable luminescent color tuning (yellow to blue including white emission) was achieved. There properties together with a persistent luminous behavior is of benefit for an irreplaceable set of optical information combination, featuring an ultrahigh‐security anti‐counterfeiting ability. Our research introduces a concept of eliminating the crystal‐form and molecular‐conformational dependence of complex luminescent properties through emitter molecular design. This has profound implications for the development of functional materials. A molecular structural strategy enabling single emitter based dual‐emission properties in various solid forms is presented. The developed amorphous films endow in situ regulation of the dual‐emissive characteristics to show highly controllable multiple luminescent color tuning (yellow to blue including white emission), which benefits to the construction of an irreplaceable set of optical information combination.